Prediction of the Passive Intestinal Absorption of Medicinal Plant Extract Constituents with the Parallel Artificial Membrane Permeability Assay (PAMPA) - Petit, Charlotte; Bujard, Alban; Skalicka-Woźniak, Krystyna; Cretton, Sylvian; Houriet, Joëlle; Christen, Philippe; Carrupt, Pierre-Alain; Wolfender, Jean-Luc (Planta Medica, 2016)
At the early drug discovery stage, the high-throughput parallel artificial membrane permeability assay is one of the most frequently used in vitro models to predict transcellular passive absorption. While thousands of new chemical entities have been screened with the parallel artificial membrane permeability assay, in general, permeation properties of natural products have been scarcely evaluated. In this study, the parallel artificial membrane permeability assay through a hexadecane membrane was used to predict the passive intestinal absorption of a representative set of frequently occurring natural products. Since natural products are usually ingested for medicinal use as components of complex extracts in traditional herbal preparations or as phytopharmaceuticals, the applicability of such an assay to study the constituents directly in medicinal crude plant extracts was further investigated. Three representative crude plant extracts with different natural product compositions were chosen for this study. The first extract was composed of furanocoumarins (Angelica archangelica), the second extract included alkaloids (Waltheria indica), and the third extract contained flavonoid glycosides (Pueraria montana var. lobata). For each medicinal plant, the effective passive permeability values Pe (cm/s) of the main natural products of interest were rapidly calculated thanks to a generic ultrahigh-pressure liquid chromatography-UV detection method and because Pe calculations do not require knowing precisely the concentration of each natural product within the extracts. The original parallel artificial membrane permeability assay through a hexadecane membrane was found to keep its predictive power when applied to constituents directly in crude plant extracts provided that higher quantities of the extract were initially loaded in the assay in order to ensure suitable detection of the individual constituents of the extracts. Such an approach is thus valuable for the high-throughput, cost-effective, and early evaluation of passive intestinal absorption of active principles in medicinal plants. In phytochemical studies, obtaining effective passive permeability values of pharmacologically active natural products is important to predict if natural products showing interesting activities in vitro may have a chance to reach their target in vivo.
Keywords: PAMPA; absorption; bioavailability; screening; natural products; medicinal extracts; passive intestinal absorption; in vitro methods